KEMAMPUAN BUNGA TELANG (Clitoria ternatea L) SEBAGAI ANTIMIKROBA (Listeria monocytogenes, Staphylococcus hominis, Trycophyton mentagrophytes, dan Trycophyton rubrum) MELALUI METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA - Maya Puspitasari; Firman Rezaldi; E.Egriana Handayani; Dedeh Jubaedah (Jurnal Medical Laboratory, 2022)
Telang flower has the ability to inhibit microbial growth in both bacterial and fungal species through the kombucha fermentation biotechnology method. The purpose of this study was to determine the antimicrobial activity of telang flower kombucha at various concentrations of white sugar. The varying concentrations of granulated sugar used in this study were 20%, 30%, and 40% (w/v), each repeated 3 times. The positive control used was kombucha made from green tea. The negative control used was sterile distilled water. The well diffusion method is one of the methods used to test antimicrobial activity. The fementation of telang flower kombucha has overall antimicrobial activity. White sugar concentration of 40% kombucha telang flower is the best concentration in inhibiting microbial growth as a whole when compared to the concentration of white sugar kombucha telang flower of 20%, 30% as well as positive and negative controls.